Fostering Engagement Through Ice Breaking in Islamic Education - Silvani, Savira Deta; Fahyuni, Eni Fariyatul (Universitas Muhammadiyah Sidoarjo, 2024)
Background: Innovative pedagogical strategies are crucial for enhancing student engagement in Islamic education. Specific Background: This study examines the implementation of ice-breaking activities to address challenges of fatigue and disengagement during the final class period at an elementary school. Knowledge Gap: There is limited research on the application of ice-breaking techniques within Islamic education contexts. Aims: The research aims to evaluate the effectiveness of ice-breaking activities in fostering a conducive learning environment. Results: Findings indicate that these activities significantly improve students’ attention and comprehension, facilitating effective lesson delivery. Novelty: This study demonstrates how tailored ice-breaking exercises can alleviate classroom fatigue and promote engagement. Implications: The results suggest that integrating ice-breaking activities can serve as a practical strategy for educators to enhance student engagement and knowledge retention, thereby cultivating a dynamic classroom atmosphere. Highlights : Enhancement of Engagement: Ice-breaking activities significantly boost student focus and participation, especially during critical learning periods. Tailored Approaches: Specific ice-breaking techniques can effectively address classroom fatigue and disengagement in Islamic education settings. Practical Teaching Strategy: Integrating these activities offers educators a valuable tool for improving instructional delivery and student comprehension. Keywords: Islamic education, ice-breaking activities, student engagement, classroom strategies, teaching effectiveness.